Design and Validity of Electronic Assessments to Assess Students Critical Thinking Abilities on Circular Motion Materials - Yuliani, Nuri; Mufit, Fatni (Universitas Negeri Padang, 2025)
Critical thinking abilities are one of the essential 21st-century abilities that students must possess. These abilities are important for training students to deal with problems, provide reasoned explanations, and evaluate the information they receive. Critical thinking abilities can be measured using appropriate assessments. However, the availability of assessments to evaluate these abilities is still limited. Therefore, the purpose of this study is to develop an electronic assessment to measure students critical thinking abilities in the topic of circular motion that meets good validity criteria. This research is a type of Research and Development (R&D) using the Plomp development model. In this study, 45 assessment items were developed, consisting of 15 diagnostic questions and 30 summative questions. The results showed that the electronic assessment developed had a validity score of V=82 for the diagnostic assessment. The validity score for the summative assessment was V=81, both categorized as very valid. Based on these results, it can be concluded that the electronic assessment for evaluating students critical thinking abilities in circular motion has met the criteria for good validity and can therefore be used to assess students critical thinking abilities effectively.